Evaluación y caracterización de ácidos orgánicos presentes en cuatro bebidas ancestrales fermentadas con preparados enzimáticos - Saigua Chilig, Pamela Estefanía (2021)
The purpose of this project was to evaluate and characterize the organic acids present in fermented beverages with enzymatic preparations of cassava (white, wiwis and burnt) and chonta. In which the best treatment of previous projects was replicated, taking into account the controlled physical parameters such as °brix, pH, acidity and alcohol content. The work was carried out by means of the elaboration of the different masates of yucca and chonta. The best treatments were "chicha blanca, wiwis and chonta" in which an enzymatic hydrolysis was applied for 80 minutes with a concentration of 0.15% of enzyme; in the burnt cassava beverage it was used with a concentration of 0.05% of enzyme for 40 minutes of hydrolysis, all of them with a fermentation of 72 hours, obtaining enzymatic acids. 05% of enzyme for 40 minutes of hydrolysis, all of them with a fermentation of 72 hours, generating the obtaining of organic acids with a percentage in the "chicha de chonta" of citric acid with a concentration of 855.56mg/100ml, malic acid 8.5mg/100ml, lactic acid 712. 27 mg/100ml; in the "chicha blanca" was found the presence of citric acid with a concentration of 25.98 mg/100ml, malic acid 36.59mg/100ml, lactic acid 802.98 mg/100ml, tartaric acid 6.51 mg/100ml ; in the "chicha wiwis" was found citric acid with a concentration of 94. 74mg/100ml, malic acid 26.71mg/100ml, lactic acid 830.58mg/100ml and tartaric acid 31.14 mg/100ml and in "chicha quemada" citric acid concentration of 49.47 mg/100ml, malic acid 37.33 mg/100ml, lactic acid 120.65 mg/100ml and tartaric acid 53.59 mg/100ml were found. In the organoleptic analysis as a result of the "chichas" very appetizing conditions and organoleptic characteristics were obtained, the organic acids involved resulted in beverages with desired acidity, appetizing odor and pleasant taste, the most predominant in the case of the chonta beverage being considered citric acid and in the case of the cassava beverages it was lactic acid. As for the comparison made with the previous projects and the current project, the beverages fermented with enzymatic preparations had similar concentrations to the project of ancestral beverages with traditional fermentation, which had high concentrations of organic acids. In the case of the beverages made in the traditional way, lactic acid had a predominance of 894.41mg/100ml in the "chicha blanca" beverage, while the beverages made with enzymatic preparations had a value of 830.58mg/100ml in the "chicha wiwis", unlike the beverage made with kefir and yeast, which had a concentration of 290.91mg/100ml in the case of the "chicha wiwis".